A reference free ultrasonic phased array to identify surface cracks in welded steel pipes based on transmissibility. (December 2018) - Zhou, Yun-Lai; Qian, Xudong; Birnie, Alistair; Zhao, Xiao-Ling
Abstract: This study aims to enhance the precision of ultrasonic phased array (UPA) testing in detecting and sizing the circumferential surface cracks near the girth welds of the steel pipes, via implementing, for the first time, the transmissibility analysis on the ultrasonic scan data. The transmissibility-based approach detects the presence of cracks or crack-like flaws, solely from the relative magnitude of the A-scan data in intact materials and in materials with a crack, and hence removes the requirement for a reference block, but retains the material characteristics. This study also proposes a new approach to detect cracks by the transmissibility between measured ultrasonic A-scan data at distinct locations. Through a relative movement of the UPA sensor, the crack depths derive from the wave propagation theory. The comparison against conventional UPA tests and measurement from replica-reproduced fracture surfaces, in seven circumferentially welded steel pipes with surface cracks produced by fatigue and fracture tests, verifies the applicability of proposed crack sizing approach. The experimental study also examines the distance threshold from the crack location, within which a reasonable accurate crack sizing remains tractable. Highlights: We propose a transmissibility treatment of the UPA A-scan data. The transmissibility of A-scan data allows direct detection of flaws without prior calibration. The crack size detected agrees well with the replica measurement.